Children and Youth in African History - Duff, SE. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
'This book is essential for anyone interested in the history of childhood and generational dynamics in Africa. This synthesis of a diverse and complex literature makes a strong case for the significance of age and generation as an analytic framework for African history. Duff has done a superb job of humanising the experiences of children by using fascinating, carefully selected case studies. It is both highly sophisticated and extremely accessible.' - Clive Glaser, University of the Witwatersrand, South Africa 'This book balances an approachable historical overview with conceptual analysis of age, gender, and generation. Featuring insightful and diverse case studies drawn from oral traditions, memoirs, interdisciplinary scholarship, and other literature, Duff's parallel discussion of ideologies and experiences of childhood and youth demonstrates why Africa matters to these debates.' - Corrie Decker, University of California, Davis, USA This textbook introduces readers to the academic scholarship on the history of childhood and youth in sub-Saharan Africa, with a particular focus on the colonial and postcolonial eras. In a series of seven chapters, it addresses key themes in the historical scholarship, arguing that age serves as a useful category for historical analysis in African history. Just as race, class, and gender can be used to understand how African societies have been structured over time, so too age is a powerful tool for thinking about how power, youth, and seniority intersect and change over time. This is, then, a work of synthesis rather than of new research based on primary sources. This book will therefore introduce mainstream scholars of the history of childhood and youth to the literature on Africa, and scholars of youth in Africa to debates within the wider field of the history of children and youth. S.E. Duff is Assistant Professor of African and World History at Colby College, USA. The author of Changing Childhoods in the Cape Colony: Dutch Reformed Church Evangelicalism and Colonial Childhood, 1860-1895 (Palgrave Macmillan, 2015), she is a historian of age and gender in nineteenth and twentieth-century South Africa and the British Empire.
1. Introduction -- 2. Age and Generation -- 3. Enslavement and Unfreedom -- 4. Race and Childhood -- 5. Schooling and Education -- 6. Work and Play -- 7. Politics and Violence -- 8. Conclusion.
Keywords: Africa-History.; Imperialism; Historiography; History-Methodology.; Ethnology-Africa.; Culture; African History; Imperialism and Colonialism; Historiography and Method; African Culture; Literature and Childhood